THE EFFECT OF RAMADAN FASTING TO BLOOD PRESSURE IN HYPERTENSIVE PATIENTS: A META-ANALYSIS - Luke, Kevin; Ferona, Nur Avina; Putri, Hana Letitia Anjani Suwardi; Harelina, Tia; Jeffri, Jeffri; Prastyo, Beny; Priandhini, Sekar Afifah; Atika, Atika (Journal of Community Medicine and Public Health Research, 2021)
Ramadan fasting is a type of time-restricted eating and drinking. Previously, a systematic review drew inconclusive effect of Ramadan fasting on blood pressure in hypertensive individuals. Therefore, this meta-analysis aims to evaluate Ramadan fasting effects on blood pressure in hypertensive individuals. This literature search was conducted in PubMed and Google Scholar. All studies assessing the effect of Ramadan fasting on blood pressure in hypertensive patients were included. Statistical analysis was performed in Review Manager 5.4. A total of 7 studies with 260 patients were analyzed. The male proportion and mean age varied from 41% to 88% and 37.5 years to 60 years, accordingly. Four studies measured blood pressure using the ambulatory method. Ramadan fasting significantly reduces systolic blood pressure (SMD=-0.77, 95%CI [-1.18”-0.36], p=0.0002) and diastolic blood pressure (SMD=-0.79, 95%CI [-1.35”-0.24], p=0.005) in hypertensive patients. Both analyses demonstrated high heterogeneity, yet the results persisted after sensitivity analysis. Publication bias was detected. Ramadan fasting reduces blood pressure among hypertensive patients. However, further and larger studies are required to justify this result.